(untitled) (Journal of Surgical Sciences, 2019)
Gastrointestinal stromal tumours are rare mesenchymal neoplasms of gastrointestinal tract with a malignant potential and unpredictable behavior and stomach is the commonest location involved. However coexistence of gastric carcinoma and GIST is very rare. A 32- year-old male patient who presented with upper abdominal dyspeptic symptoms, was evaluated with Upper GI Endoscopy which revealed an ulcerated lesion in the antral part of the stomach. Biopsy was taken and histopathological examination revealed the lesion as poorly differentiated adenocarcinoma. Distal radical gastrectomy revealed another 3cm of submucosal mass of GIST along with the existing adenocarcinoma. Journal of Surgical Sciences (2015) Vol. 19 (1) : 31-34